Reach and dissemination channels of (selected) disinformation narratives in Serbia - Dinko Gruhonjić; Stefan Janjić; Jelena Kleut (Političke Perspektive)
The phenomenon of disinformation has been extensively studied, with its roots traced to shifts in the media economy, declining trust, and rising political polarization and populism. Although there is a growing research on disinformation, the issues of its dissemination and reach remain contested. This study investigates the reach and dissemination channels of selected disinformation narratives in Serbia. Through a survey-based approach (N=800), the research examines seven such cases identified through fact-checking portals: alleged Russian aid superiority, alleged Ukrainian biolabs, purported Western cultural censorship, supposed Soros’s global influence, claimed Serbian-Sanskrit connections, alleged Western origins of COVID-19, and misrepresented UN policies on sexuality. The findings reveal a significant reach of these narratives, with four out of seven being recognized by over half of the respondents. Variations in exposure and belief across different narratives potentially stem from factors such as ideological alignment, plausibility, timing, and the presence of counter- narratives. A “market” of disinformation exists on TV, digital news services, and social media, while traditional press and radio play an almost negligible role in disseminating these narratives. This research adds to the growing body of work examining disinformation in illiberal contexts. It provides initial observations on how false information circulates in a media environment where political control is prevalent and media independence is under pressure, pointing to areas for future research in this complex field.